Cosmos sketch of a physical description of the universe - Humboldt, Alexander von 1769-1859 (Cambridge University Press, 2011)
Polymath Alexander von Humboldt, a self-described 'scientific traveller', was one of the most respected scientists of his time. Humboldt's wanderlust led him across Europe and to South America, Mexico, the US, & Russia, & his voyages & observations resulted in the discovery of many species previously unknown to Europeans. Originating as lectures delivered in Berlin & Paris (1827-1828), his multi-volume Cosmos: Sketch of a Physical Description of the Universe (1845-1860) represented the culmination of his lifelong interest in understanding the physical world. Volume 2 reviews poetic descriptions of nature as well as landscape painting from antiquity through to modernity, before using the same time-span to examine a 'history of the physical contemplation of the universe'.